Peningkatan Pengetahuan Ayah dalam Mencegah Kejadian Stunting Melalui Kelas Ayah - Nelyta Oktavianisya; Sugesti Aliftitah (Jurnal Ilmiah STIKES Yarsi Mataram, 2024)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life. Preventing stunting in children using a family approach consists of three strategies: proper feeding, parenting patterns, and correct hygiene and sanitation practices. Father involvement in caring for toddlers can improve toddlers' health and help prevent stunting. The aim of the research was to determine the effect of father's class on increasing father's knowledge in preventing stunting. The research design is pre-experimental, one group pre-post test design. The sample in this study was 20 respondents with the sampling technique used was purposive sampling technique. The independent variable is education about stunting through father's class and the dependent variable is knowledge level. The tool used to measure the level of knowledge is a questionnaire. The data was processed using the Paired Samples T Test. The research results showed that there was an increase in the average knowledge after being given treatment 75.20, and the standard deviation was 7.885. The results of pretest-posttest knowledge data analysis using the Paired Samples T Test, the p-value is 0.001 with α=0.05. Because the p-value <α means that there is an influence of father's class on father's knowledge in preventing stunting. By taking Dad's class, Dad will be involved in stunting prevention ABSTRAK Stunting merupakan kondisi gagal tumbuh pada anak balita akibat kekurangan gizi kronis terutama pada  1.000 Hari Pertama Kehidupan (HPK). Pencegahan stunting pada anak dengan pendekatan keluarga terdiri dari tiga strategi yaitu pemberian makan yang tepat, pola asuh, dan praktik higiene-sanitasi yang benar. Keterlibatan ayah dalam pengasuhan balita dapat meningkatkan kesehatan balita dan membantu mencegah stunting. Tujuan penelitian untuk mengetahui pengaruh kelas ayah terhadap peningkatan pengetahuan ayah dalam mencegah stunting. Desain penelitian adalah pra-eksperimental, one group pra-post test design. Sampel dalam penelitian ini 20 responden dengan teknik pengambilan sample yang digunakan yaitu teknik purposive sampling. Variabel bebas yaitu Edukasi tentang stunting melalui Kelas Ayah dan variable terikat yaitu Tingkat Pengetahuan. Alat yang digunakan untuk mengukur tingkat pengetahuan adalah kuesioner. Data diolah dengan Uji  Paired Samples T Test. Hasil penelitian didapatkan Terjadi peningkatan pada rata-rata pengetahuan setelah diberikan perlakuan yaitu 75,20, dan standar deviasi 7,885. Hasil analisis data pretest-posttest pengetahuan menggunakan uji Paired Samples T Test,  nilai p-value yaitu 0,001 dengan α=0,05. Karena nilai p-value<α maka berarti ada pengaruh kelas ayah terhadap pengetahuan ayah dalam mencegah stunting. dengan mengikuti kelas Ayah maka ayah ikut terlibat dalam pencegahan stunting.